No place in the world. The Venezuelan magical State and its petrocine - QUINTERO VILLALOBOS, Sonia (Utopía y Praxis Latinoamericana, 2024)
This work seeks to problematize the politics of film memory in Venezuela in relation to oil. On the one hand, Venezuelan cinema will be analyzed as petrocine (Fornoff) with the aim of historicizing it within an infrastructure of modernity. On the other hand, and beyond a systemic dependence, it is intended to point out its historical and material relationship based on how it was able to energize micropolitical practices protected by the Venezuelan magical State (Coronil) and how it has been historically promoted as a discourse.